Contribution of Local Tax and Retribution to Local Own-source Revenue in East Luwu Regency - Fikri Yatul Hasanah; Wardihan Sabar (Bulletin of Economic Studies (BEST), 2021)
Local Own-source Revenue is an important element in regional economic development. This study describes the contribution of various types of regional taxes and levies to Local Own-source Revenue in East Luwu Regency for the 2015-2019 period. This research is descriptive quantitative. The data used is secondary data sourced from the local Financial Management Agency of East Luwu Regency and the Central Statistics Agency of East Luwu Regency. The analytical method used is contribution analysis which is an analytical tool to find out how much the contribution of local taxes and levies to local revenue in East Luwu Regency. The results show that the contribution of local taxes as a whole gives a very good contribution to local revenue in East Luwu Regency, and the type of tax with the largest contribution to local revenue comes from taxes on non-metallic minerals and rocks. Meanwhile, the contribution of regional retribution as a whole still provides a very low level of contribution to regional original income in East Luwu Regency. Among the various types of retribution, the largest contribution to local revenue comes from retribution for licensing servicesKeywords: Local Taxes, Local Levies, Local Own-source Revenue, East Luwu Regency